MAKNA TEOLOGIS DAN APLIKASI DARI STRATEGI PEMBELAJARAN YAHUDI UNTUK PENDIDIKAN AGAMA KRISTEN MASA KINI - Yusak Tanasyah; Antonius Missa (Sekolah Tinggi Teologi Moriah, 2021)
The Jewish nation, which has been present for thousands of years in the world, has had no small influence on the development of mankind, especially in the field of education. Jews who have the same holy book or God's law as Christianity, which is sourced from the Torah, provide guidelines and implementation of how to carry out education that is applicable and useful for mankind. The Torah which is the source and guidance is a book that is taught and applied in the daily life of the Jewish people. The question is what learning strategies are used in implementing and carrying out education? Learning strategies are important to know because they involve how to bring learning to students to be more effective. Learning strategies provide content and creativity as well as core values ??to students to capture messages conveyed from educators to students. Christian religious education cannot escape the meaning and application of Jewish learning strategies as it has the same foundation in the law or the word of God. The method used in this study is qualitative research sourced from literature originating from books, journals, and data from internet media which is formulated to be applied for today. Bangsa Yahudi yang ribuan tahun hadir di dalam dunia telah memberikan pengaruh besar atas perkembangan manusia khususnya di dalam bidang Pendidikan. Yahudi yang memiliki kitab suci atau dan hukum Tuhan yang sama dengan kekristenan yang mana bersumber dari Taurat memberikan pedoman dan pelaksanaan bagaimana menjalankan pendidikan yang aplikatif dan berguna bagi umat manusia. Taurat yang adalah sumber dan petunjuk merupakan kitab yang diajarkan dan diterapkan dalam kehidupan sehari-hari umat Yahudi. Pertanyaannya adalah strategi pembelajaran apakah yang dipakai dalam menerapkan dan menjalankan pendidikan? Strategi pembelajaran menjadi penting untuk diketahui karena menyangkut bagaimana membawa pembelajaran kepada peserta didik untuk lebih efektif. Strategi pembelajaran memberikan muatan dan kreatifitas serta nilai inti kepada peserta didik untuk menangkap pesan yang disampaikan dari pendidik ke peserta didik. Pendidikan agama Kristen tidak dapat melepaskan diri dari makna dan penerapan dari strategi pembelajaran orag Yahudi sebagaimana memiliki pondasi yang sama di dalam hukum atau firman Allah. Metode yang digunakan dalam penelitian ini adalah penelitian kualitatif yang bersumber dari literatur yang berasal dari buku, journal dan data dari media internet yang dirumuskan untuk diambil aplikasinya bagi masa kini.